SISTEM INFORMASI PERSALINAN DENGAN METODE SCRUM - Dian Lestari; Tantri Hidayat Sinaga; Nurjamiyah Nurjamiyah (Jurnal Media Informatika, 2022)
In today's modern era, information technology has had a considerable influence in many ways, especially in the world of health. In this study, there were several problems related to labor management at the Tinggi Raja Health Center such as recording examinations related to childbirth examinations such as recording actions, blood pressure, fetal position, weight and size of the fetus as well as submitting a schedule then missing examination cards, examinations that were missing. irregular and this examination will of course take a lot of time, especially in finding patient data because all activities are still recorded in the ledger and will hinder the ongoing examination process, the results of the examination are only recorded with an examination card, information related to childbirth is still displayed on the walls of the health center. The purpose of this study is to build a labor management system using the scrum method. With this system, it can be used in patient data collection, and makes it easier for the public to carry out obstetrical examinations and so that puskesmas patients can predict childbirth so that it can make it easier for the community to submit a delivery schedule.